MMAB promotes negative feedback control of cholesterol homeostasis - Leigh Goedeke (Nature Portfolio, 2021)
The mechanisms governing cholesterol homeostasis remain incompletely understood. Here, the authors develop an integrative genomic strategy to identify MMAB, and enzyme in the adenosylcobalamin pathway, as a regulator of hepatic LDLR activity and cholesterol biosynthesis.